2014
DOI: 10.1007/s11814-014-0213-1
|View full text |Cite
|
Sign up to set email alerts
|

The performance of pelletized Ce-Y and Ni-Y zeolites for removal of thiophene from model gasoline solutions

Abstract: H-Y zeolite was prepared with Na-Y zeolite via ion-exchange method. Ni-Y and Ce-Y zeolites were then prepared with H-Y zeolite via solid-state ion-exchange (SSIE) method. The pellet form of the zeolites was employed for removal of thiophene from samples containing 194, 116 and 72 ppmw sulfur in a batch system at ambient condition. The removal of sulfur over the three types of the adsorbents decreased according to the following order: Ce-Y (81.7%) >Ni-Y (75.2%)>Na-Y (51.7%), indicating that the Ce-Y zeolite was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To develop a proper adsorbent, many studies have been performed using metal oxides [ 22 , 23 ], carbon-based materials [ 24 , 25 , 26 ] as well as zeolites and their metal-loaded derivatives [ 27 , 28 ]. Among these materials, Y-type zeolites have been investigated widely due to their high surface area, size-selective adsorption capacity, high ion-exchange capacity, and good thermal stabilities [ 29 , 30 ]. Yang and his co-workers [ 12 , 13 , 28 , 31 , 32 ] explored Ag-, Cu-, Ni-, and Zn-exchanged Y zeolites, which exhibited a high sulfur adsorption capacity for thiophenic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a proper adsorbent, many studies have been performed using metal oxides [ 22 , 23 ], carbon-based materials [ 24 , 25 , 26 ] as well as zeolites and their metal-loaded derivatives [ 27 , 28 ]. Among these materials, Y-type zeolites have been investigated widely due to their high surface area, size-selective adsorption capacity, high ion-exchange capacity, and good thermal stabilities [ 29 , 30 ]. Yang and his co-workers [ 12 , 13 , 28 , 31 , 32 ] explored Ag-, Cu-, Ni-, and Zn-exchanged Y zeolites, which exhibited a high sulfur adsorption capacity for thiophenic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…6 Among these compounds, Th and benzocyclothiophene compounds are difficult to remove by traditional HDS technology because of their high steric hindrance and good molecular stability. 7,8 Therefore, the key to deep desulfurization of gasoline lies in the removal of Ths and benzothiophenes (BTs). At present, nonhydrodesulfurization technologies for desulfurization in-clude adsorption desulfurization, 9−11 extractive desulfurization (EDS), 12−14 biological desulfurization, 15−17 oxidative desulfurization (ODS), 18−20 photocatalytic ODS, 21−24 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Th sulfur compounds are mainly distributed in the 60–100 °C fraction and macromolecular Th and benzocyclothiophene sulfides are mainly distributed in the heavy fraction . Among these compounds, Th and benzocyclothiophene compounds are difficult to remove by traditional HDS technology because of their high steric hindrance and good molecular stability. , …”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of adsorbents including activated alumina, metal oxides, mesoporous silica, metal organic frameworks (MOFs), zeolites, , and activated carbon have been explored for adsorptive desulfurization. It was suggested that adjusting the textural properties of adsorbents is the primary strategy for improving adsorptive performance.…”
Section: Introductionmentioning
confidence: 99%